2019
DOI: 10.3390/ijms20184425
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Combined Genetic Engineering Vaccine for Porcine Circovirus Type 2 and Mycoplasma Hyopneumoniae by a Baculovirus Expression System

Abstract: Mycoplasma hyopneumoniae (Mhp) and porcine circovirus type 2 (PCV2) are the main pathogens for mycoplasmal pneumonia of swine (MPS) and post-weaning multisystemic wasting syndrome (PMWS), respectively. Infection by these pathogens often happens together and causes great economic losses. In this study, a kind of recombinant baculovirus that can display P97R1P46P42 chimeric protein of Mhp and the capsid (Cap) protein of PCV2 was developed, and the protein location was identified. Another recombinant baculovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Among them, the development of enhancing the immunogenicity of the PCV2 subunit vaccine is particularly important. PCV2 capsid (Cap) protein is a viral nucleocapsid protein encoded by open reading frame 2 (ORF2) and contains specific antigenic determinants [8]. The Cap protein is the major immunogenic structural protein of PCV2 and is responsible for neutralizing antibodies and inducing humoral and cellular immunity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the development of enhancing the immunogenicity of the PCV2 subunit vaccine is particularly important. PCV2 capsid (Cap) protein is a viral nucleocapsid protein encoded by open reading frame 2 (ORF2) and contains specific antigenic determinants [8]. The Cap protein is the major immunogenic structural protein of PCV2 and is responsible for neutralizing antibodies and inducing humoral and cellular immunity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The baculovirus-produced N-Terminal Pfs230 domain was also studied as a biological active transmission-blocking vaccine candidate to accelerate malaria parasite elimination (Lee et al, 2017). A baculovirus expression system was also used for the development of a combined genetic engineering vaccine for Porcine Circovirus type 2 and Mycoplasma hyopneumoniae (Tao et al, 2019). In one study, Hantaan virus-like particles were successfully produced by co-expressing Hantaan virus nucleocapsid (N) protein and glycoproteins (Gn and Gc) in Sf9 cells for vaccine studies, and it was shown that the purified VLPs provided protection from virus challenge in mice (Dai et al, 2019).…”
Section: Insect Cellsmentioning
confidence: 99%
“…Despite some research groups having demonstrated that baculovirus vectors can be used to induce adaptive immune responses against heterologous viral antigens in swine [51][52][53][54][55], their ability to induce the production of IFNs by porcine immune cells in the short term has never been studied before. Since baculoviruses could have distinct immunomodulatory capacities in mice and other hosts, the purpose of this work was to study the potential of AcMNPV to induce a rapid production of IFNs, especially those of type I, in porcine mononuclear cells.…”
Section: Introductionmentioning
confidence: 99%